RESOLUTION-ENHANCEMENT FOR CONFOCAL SCANNING FLUORESCENCE MICROSCOPY USING TWO DIFERENT POINT SPREAD FUNCTIONS WITH THE LOGARITHM -MULTIPLYING RELATIONSHIP - Nhu (Journal of Military Science and Technology, 2020)
In this paper, one method improving the resolution of confocal scanning fluorescence microscopy has been suggested. One image is achieved by using Gaussian beam, other image is acquired by employing doughnut beam. The high-resolution image can be achieved from the logarithm-multiplying relationship of the two images. The simulation and experimental results are presented. The results demonstrated that the proposed method can be used to improve the resolution of confocal scanning fluorescence microscopy.